Tax Systems and Tax Reforms in New EU Member States - Bernardi, Luigi; Chandler, Mark; Gandullia, Luca (Routledge Studies in the Modern World Economy, 2005)
Building on the work carried out in the 2004 Routledge book, Tax Systems and Tax Reforms in Europe, an international team of contributors now turn their attention to the new EU member states. The book compares conditions in the new and potential EU Member states to those in the long-standing EU countries. Topics covered include: * A Comparative View of Taxation in the EU and in New Members * Tax Policy in EU New Members * Tax Policy in New Members under the Stability Pact * Tax Administration and the Black Economy. As well as investigating countries such as the Czech Republic, Estonia and the Baltics, Hungary, Poland and Slovenia, this outstanding book contains a foreword by Vito Tanzi and will be a valuable resource for postgraduates and professionals in the fields of economics, politics, finance and European studies.